Pragmatic Philanthropy Asian Charity Explained - Shapiro, Ruth A. (Springer Singapore, 2018)
This book is open access under a CC BY 4.0 license. This cutting edge text considers how Asian philanthropists and charitable organizations break with Western philanthropic traditions and examines the key traits and trends that make social investment in Asia unique. Based on 30 case studies of excellent social delivery organizations (SDOs) and social enterprises as well as interviews with ultra-high net-worth individuals throughout Asia, this book examines which characteristics and strategies lead to successful philanthropy and social delivery organizations. Providing evidence based findings on philanthropy, social investment and social delivery organizations in Asia, this book provides invaluable resources for those wishing to deepen their understanding of the sector and what this means for political and economic development in the region.